Psychological Capital and Business Success of Chinese, Minangnese, and Javanese Entrepreneurs - Andri*, Nofri; Ronauli*, Puji Tania; Riyanti*, Benedicta P. Dwi (Universitas Prasetiya Mulya, 2019)
Psychological capital (Psycap) is a condition of positive psychology (hope, efficacy, resilience, and optimism), which facilitates entrepreneurs to survive in running and reach success in their business. This research was intended to obtain the overviews of psycap and business success of Chinese, Minangnese, and Javanese entrepreneurs. There was a total of 207 entrepreneurs involved as respondents. There were two instruments used in this study: the Psychological Capital Scale and the Balanced Scorecard. Data analysis method applied to measure psychological capital was a descriptive statistic. The result showed that Javanese entrepreneurs had a very high level of psychological capital, while both Chinese and Minangnese entrepreneurs hold on the same high degree. Meanwhile, the data analysis regarding the successfulness of business showed that most of the Javanese entrepreneurs reached a high level of success, Chinese entrepreneurs were average, and Minangnese entrepreneurs were low.Keywords:Psychological Capital, Business Success, Entrepreneur, Chinese, Minangnese, Javanese*Faculty of Psychology, Atma Jaya Catholic University of Indonesia, Jl. Jend. Sudirman 51, Jakarta Selatan 12930, DKI Jakarta, Indonesia. https://doi.org/10.21632/irjbs.12.2.157-166